Sosialisasi Tentang Manfaat Pijat Bayi Terhadap Durasi Menyusui - Nikmah Jalilah Ritonga; Kardina Hayati (Yayasan Daarul Huda Kruengmane, 2026)
In addition to serving as a source of nutrition, breastfeeding also enhances infant intelligence and strengthens the emotional bond between mother and baby. The benefits of breastfeeding increase when exclusive breastfeeding is maintained for the first six months of life, as recommended in Indonesia's National Medium-Term Development Plan (RPJMN) 2015–2019. The duration of breastfeeding varies depending on the infant's sucking pattern. If breastfeeding lasts too long (more than 30 minutes) or too briefly (less than 4 minutes), it may indicate problems with the baby's latch onto the mother's nipple. The frequency of breastfeeding greatly influences the infant's physical and emotional health. Appropriate breastfeeding frequency and duration can improve the baby's comfort and support healthy weight gain. One strategy to enhance infant comfort and promote weight gain is through infant massage. This community service program (PKM) was conducted in Bandar Khalipah Village, Percut Sei Tuan, and included educational sessions, question-and-answer discussions, and hands-on infant massage training. The results of the program demonstrated positive benefits, as reflected in the mothers' improved understanding and favorable responses to the educational materials presented. It can therefore be concluded that this community service activity successfully increased mothers' knowledge regarding efforts to optimize infant growth and development through the practice of infant massage, which may influence breastfeeding duration. It is expected that, following this program, breastfeeding mothers will be able to perform infant massage independently at home as part of their efforts to support their babies' optimal growth and development.